Age‐dependent brain volume and neuropsychological changes after chemotherapy in breast cancer patients. Issue 17 (21st August 2019) - Blommaert, Jeroen; Schroyen, Gwen; Vandenbulcke, Mathieu; Radwan, Ahmed; Smeets, Ann; Peeters, Ron; Sleurs, Charlotte; Neven, Patrick; Wildiers, Hans; Amant, Frédéric; Sunaert, Stefan; Deprez, Sabine
Abstract: This study investigated volumetric brain changes and cognitive performance in premenopausal and postmenopausal patients treated for early‐stage breast cancer. Participants underwent elaborate neurocognitive assessments (neuropsychological testing, cognitive failure questionnaire, and high‐resolution T1‐weighted structural MRI) before and after chemotherapy. Volumetric brain changes were estimated, using longitudinal deformation‐based morphometry, and correlated with cognitive changes. In total, 180 women participated in this study, of whom 72 patients with breast cancer had received adjuvant chemotherapy (C+), 49 patients did not receive chemotherapy (C−), and 59 healthy controls (HC). The population was categorized into two age groups: A young group who were premenopausal and younger than 52 years at baseline ( n = 55C+/32C−/41HC), and an older group who were postmenopausal and older than 60 years ( n = 17C+/17C−/18HC). Cognitive impairment occurred after chemotherapy in both young and older patients, although older patients showed more decline in processing speed (Trail making test b). White matter volume expansion was observed after chemotherapy, only significantly present in the younger subgroup of patients. In patients not treated with chemotherapy, diffuse gray and white matter volume reduction was observed. Less white matter expansion concurred with more cognitive decline ( r  > .349, p  < .05). In conclusion, we found age‐dependent cognitive decline and white matter volume changes in patients with breast cancer after chemotherapy, which could possibly be linked to neuroinflammatory processes. White matter expansion after chemotherapy, more pronounced in premenopausal patients, correlated with less cognitive decline. This suggests such expansion to be age‐dependent, possibly caused by a protective response in the younger brain to chemotherapy‐induced neurotoxicity.